Evaluation of cyanotoxin L-BMAA effect on α-synuclein and TDP43 proteinopathy - Sini, Paola; Galleri, Grazia; Ciampelli, Cristina; Galioto, Manuela; Padedda, Bachisio Mario; Lugliè, Antonella; Iaccarino, Ciro; Crosio, Claudia (Frontiers in Immunology, 2024)
The complex interplay between genetic and environmental factors is considered the cause of neurodegenerative diseases including Parkinson's disease (PD) and Amyotrophic Lateral Sclerosis (ALS). Among the environmental factors, toxins produced by cyanobacteria have received much attention due to the significant increase in cyanobacteria growth worldwide. In particular, L-BMAA toxin, produced by diverse taxa of cyanobacteria, dinoflagellates and diatoms, has been extensively correlated to neurodegeneration. The molecular mechanism of L-BMAA neurotoxicity is still cryptic and far from being understood. In this research article, we have investigated the molecular pathways altered by L-BMAA exposure in cell systems, highlighting a significant increase in specific stress pathways and an impairment in autophagic processes. Interestingly, these changes lead to the accumulation of both α-synuclein and TDP43, which are correlated with PD and ALS proteinopathy, respectively. Finally, we were able to demonstrate specific alterations of TDP43 WT or pathological mutants with respect to protein accumulation, aggregation and cytoplasmic translocation, some of the typical features of both sporadic and familial ALS..